Bioinspired Materials: Bioinspired Color Materials Combining Structural, Dye, and Background Colors (Small 30/2018). Issue 30 (26th July 2018) - Sakai, Miki; Seki, Takahiro; Takeoka, Yukikazu
Abstract : In article number1800817, Yukikazu Takeoka and co‐workers show the preparation and optical properties of a composite color material combining photochromic dyes, a black substance, a spherical colloidal crystal exhibiting a structural color, and a background color, inspired by the extraordinary body color changes of living things. The contribution of the different effects of the background color on each coloring property allows for the construction of a color material that can reversibly change into various colors under different conditions.